The impact of death and dying on surgeons in a tertiary cancer centre in Singapore - Si Ying Tan; Jun Rong Tan; Yun Ting Ong; Yaoyi Ng; Annushkha Sinnathamby; Nur Amira Binte Abdul Hamid; Simon Yew Kuang Ong; Lalit Kumar Radha Krishna (BMC Surgery)
Abstract Background Demands upon surgeons are increasing, especially in the care of the terminally ill. Fronting patient care, supporting families and guiding multi-disciplinary care teams facing the loss of patients see surgeons experiencing moral distress, compassion fatigue, vicarious trauma and secondary traumatic stress with the blurring of professional and personal boundaries. The full extent of these ‘costs of caring’ upon a surgeon remains unclear despite evidence of their compromises to patient care. To understand the costs of caring, semi-structured interviews are proposed to achieve the primary aim of understanding ‘What is known about the costs of caring on surgeons in Singapore?’ and the secondary aim, ‘What is the impact of the costs of caring on a surgeon’s professional identity?’. Methods Twelve surgeons of various subspecialties from a tertiary cancer centre in Singapore were interviewed between 21st June 2022 and 18th December 2023. Transcripts were analysed using Krishna’s Systematic Evidence-Based Approach. Results The key domains identified were: (1) motives for surgical career; (2) forms of emotional distress experienced; (3) impact of challenging experiences on personhood; and (4) buffer mechanisms. Conclusions The costs of caring impact surgeons’ professional identities; shape their ‘internal compasses’ or the way they deliberate and assess their responsibilities; and influence patient safety and family support. The costs of caring and the ‘internal compass’ are moulded by the surgeon’s traits, maturing competencies, growing insights, clinical experience and sociocultural context. Without holistic, longitudinal and personalised support in both the personal and professional spheres, the costs of caring compromise surgeons’ confidence and professional identities.